Sociology and health care an introduction for nurses, midwives and allied health professionals - Sheaff, Michael; Sheaff, Michael (Maidenhead, England ; New York : Tata Mcgraw Hill Education Private Limited, 2010)
"The book provides suggestions and examples of how sociological concepts and insights can be used to help think about important contemporary issues in health care. For that reason, it has a practical as well as academic purpose, contributing to the improvement of the quality of interaction between patients and practitioners. The core themes running throughout the book are inequalities in health and the rise of chronic disease, with particular attention being given to psycho-social models of illness which locate individual experiences within wider social relationships." "Sociology and Health Care is key reading for student nurses and those on allied health courses, and also appeals to a wide range of professionals who are interested in current debates in health and social care."--BOOK JACKET.
Inequality and access to health care.
Includes bibliographical references (p. [234]-246) index.
Includes bibliographical references (p. [234]-246) index.
All age.
Keywords: Social medicine -- Great Britain; Sociology, Medical; Delivery of Health Care; Médecine sociale -- Grande-Bretagne.